Analysis of Fats and Fatty Acids in Several Bakery Cookies of Bangladesh (Dhaka University Journal of Science, 2022)
Cookie is one of the most common baked goods consumed by people throughout the globe including in Bangladesh. Cookies have a considerable amount of fats, despite not being considered as fatty foods by consumers. Since cookies are eaten by individuals of all ages and socioeconomic groups, an experimental investigation was conducted to evaluate the quality and quantity of the fat fraction of bakery cookies available in Dhaka. Ten different bakery cookies (5 savory and 5 sweet) from five different manufacturers were collected from several local supermarkets of Dhaka and analyzed to study the total fat contents, relative fatty acids compositions, moisture and ash contents. Extraction of fat from cookie samples was done using n-hexane. The fatty acid compositions of the samples were determined by gas-liquid chromatograph equipped with flame ionization detector. The results showed the total fat content to be ranged from 16.13-26.84 g/100g of cookies. The fatty acid composition exhibited that the relative percentage of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) were in the range of 7.76-78.20, 9.66-79.56 and 0.38-9.64%, respectively. The major FAs were found to be palmitic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1) and linoleic acid (C18:2). The moisture and ash contents in the samples were found in the range of 0.79-4.80 and 0.73-4.23%, respectively.Dhaka Univ. J. Sci. 70(2): 53-58, 2022 (July)